Adaptation of a vocabulary test from British Sign Language to American Sign Language. (January 2016) - Mann, Wolfgang; Roy, Penny; Morgan, Gary
This study describes the adaptation process of a vocabulary knowledge test for British Sign Language (BSL) into American Sign Language (ASL) and presents results from the first round of pilot testing with 20 deaf native ASL signers. The web-based test assesses the strength of deaf children's vocabulary knowledge by means of different mappings of phonological form and meaning of signs. The adaptation from BSL to ASL involved nine stages, which included forming a panel of deaf/hearing experts, developing a set of new items and revising/replacing items considered ineffective, and piloting the new version. Results provide new evidence in support of the use of this methodology for assessing signed languages, making a useful contribution toward the availability of tests to assess deaf children's signed language skills.